Thin Films Prepared from Nanometer Size TiO2 Absorbs Millimeter Waves. (11th November 2012) - Yesil, Mehmet Ali; Yegin, Korkut; Culha, Mustafa; Efeoglu, Esen
Abstract : Absorption of average 10 nm size TiO2 nanoparticles deposited on glass surfaces as a thin film using convective assembly technique and drop-casting is studied in the millimeter wave range from 26 GHz to 40 GHz. The millimeter wave responses of the fabricated samples were obtained using a vector network analyzer. Reflection properties of the prepared samples were also measured. Absorption and reflection of TiO2 nanoparticles were more pronounced between 35 GHz and 40 GHz compared to glass-only sample.